Digital Transformation by Data Fabric - Anand, J. V. (IRO Journal on Sustainable Wireless Systems, 2022)
Many industries, including financial sector, telecommunications, transportation, and health care, are paying increasing attention to enterprise data fabrics. The continuous data expansion that enterprises are currently experiencing is being driven by digital transformation. As businesses adopt hybrid and multicloud settings, there is a big opportunity for managing data, but it has also greatly increased complexity. A data fabric is a concept that data executives are working over more and more, when it comes to choosing an architecture that supports and improves the data strategy. Enterprise data fabrics, which offer a distributed, functional data platform positioned between software architectures and back-end datasets, are built towards high performance and reliability.